Pembinaan Akhlakul Karimah dengan Mengaplikasikan Nilai-Nilai Keagamaan - Muhammad Ali (GHIROH, 2022)
Instilling religious values ​​in one's self should start early, even the Prophet Muhammad (PBUH) suggested that it is better to educate children starting from someone starting to look for a mate (partner) in his life. In the family the inculcation of religious values ​​is carried out by both parents. When a child enters an educational institution, the task of coaching is continued by the education staff (teachers) at the school. The desire of parents for their children to have good morals is their goal because children who have noble character will behave well towards others and towards their parents. The existence of teachers in schools and even Islamic religious teachers is expected to provide an example of morality to students. Moral development for junior high school students is carried out continuously. The application and development of Islamic religious learning values ​​is expected to be a bridge in the formation of morality.